Galapa: Your History, my Present, our Future; Cultural Heritage as Pedagogical Strategy Available to All - Meca Ospina, Johnny (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This text is the result of a research process carried out with the people of the municipality of Galapa, in the Department of Atlántico, about their cultural heritage which allowed to open spaces for dialogue and to contribute through divulgation and education about the cultural reality of such territory. The text describes the experience thanks to which spaces such as the museum and the library were used as contact zones, so that different group could talk about the everyday activities that are now considered as their cultural heritage. Through activities that criticize the current methodologies of inventory and record, it was demonstrated that effective participation of civil society can be gained in order to foster a pluralistic dialogue – instead of an academic and institutional monologue – which helps to identify the way in which communities interpret, explain and assume their traditional knowledge; and then design tools contributing to transmission and disclosure of such knowledge.